PENGARUH PEMBELAJARAN SENI TARI BERBASIS METODE DRILL TERHADAP KEMAMPUAN MOTORIK KASAR SISWA DI KELAS V SD TUNAS HARAPAN - Khadijah Gani Harahap; Putra Afriadi; Tiarnita Maria Sarjani Br. Siregar; Try Wahyu Purnomo; Sri Mustika Aulia (STKIP Subang, 2026)
This study aims to determine the effect of the Drill Method on Gross Motor Skills of Students in Grade V of Tunas Harapan Elementary School. This type of research is quantitative research. The research method used is Pre-Experiment with One Group Pretest and Posttest Design. The population used is grade V of Tunas Harapan Elementary School, which consists of 25 students. The sampling technique used is saturated sampling technique because the population in grade V students is less than 30 people. Data collection techniques used are interviews and observation sheets. Based on the results of the research and data analysis, it can be seen that the pre-test or test before being given the drill method treatment for the experimental class has an average value of 55.84 and the control class has an average value of 56. While the post-test for the experimental class has an average value of 76.23 and the control class has an average value of 71.66. Hypothesis testing was carried out using the Paired Sample T-Test. The test results obtained a value of 0.001 which means it is smaller than 0.05 (0.000 <0.05). This shows that Ho is rejected and Ha is accepted, so it can be concluded that dance arts learning based on the drill method can improve the gross motor skills of students in grade V of Tunas Harapan Elementary School.